Analisis Hubungan Antara Pertumbuhan Penduduk dan Per Capita Real GDP - Razali Abdullah (SI-MEN, 2016)
This study aimed at analyzing the level of population growth and quality standard of living. The instrument used to collect the data of this study was qualitative descriptive approach model calculated time series and panel data of adjusted for 56 countries worldwide derived by Van Den Berg ( 2005 ). The result of study shows that the rate of population growth very gradually accelerated from zero to less than one–half of 1 per cent per year, but per capita real income remained virtually unchanged. The chances that 1oo years from now people will still be suffering from levels of income below 1 thousand USD per year, as is the case for so many people throughout the developing world today are not high. It would take growth rates of 0 per cent for this to happen. One century is not very much time in the course of human history.